2017
DOI: 10.1021/acs.jpcc.7b03752
|View full text |Cite|
|
Sign up to set email alerts
|

Orientation of Methylguanidinium Ions at the Water–Air Interface

Abstract: We use heterodyne-detected vibrational sum-frequency generation (HD-VSFG) to determine the orientation of the molecular plane of methylguanidinium ions at the surface of aqueous solutions. We measure the VSFG response of the symmetric and antisymmetric methyl stretch vibrations of the methylguanidinium ion with different polarization combinations. We find that for at least 50% of the methylguanidinium ions the molecular plane is at an angle >20° with respect to the surface plane. Hence, for only a minor fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
3
17
3
Order By: Relevance
“…The orientation of its molecular plane at the interface thus becomes an interesting topic, and has been investigated by many theoretical and experimental studies. A recent VSFG experiment found that a large fraction of M-Gdm + ions have an angle relative to the interface, 24 conflicting with previous MD simulaitons which predicted that most interficial M-Gdm + ions lie parellel to the interface. [25][26][27] Key observable from the VSFG measurement is the ensemble averaged D value determined by the orientation of the M-Gdm + methyl group with respect to the air/water interface.…”
Section: B Orientational Preference At the Interfacementioning
confidence: 60%
See 2 more Smart Citations
“…The orientation of its molecular plane at the interface thus becomes an interesting topic, and has been investigated by many theoretical and experimental studies. A recent VSFG experiment found that a large fraction of M-Gdm + ions have an angle relative to the interface, 24 conflicting with previous MD simulaitons which predicted that most interficial M-Gdm + ions lie parellel to the interface. [25][26][27] Key observable from the VSFG measurement is the ensemble averaged D value determined by the orientation of the M-Gdm + methyl group with respect to the air/water interface.…”
Section: B Orientational Preference At the Interfacementioning
confidence: 60%
“…Molecular orientation. The key result from HD-VSFG measurements is an ensemble averaged D value determined by the orientation of the M-Gdm + methyl group at the air/water interface 24 D = cos 3 θ CH 3 cos θ CH 3 (1) , where θ CH 3 is the angle between the methyl C 3 axis and the surface normal. Another variable to describe the molecular orientation of M-Gdm + at the interface would be the angle θ MP between the molecular plane and the surface normal.…”
Section: B Analysis Of MD Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Strazdaite and co-workers used heterodyne-detected vibrational sum frequency generation (HD-VSFG) to examine the methyl stretch vibration of M-Gdm + , and found that a large fraction of ions adopt certain tilt angles at the air/water interface. 24 This contrasts with previous simulation studies, [25][26][27] which found that Gdm + has a orientational preference of being parallel to the air/water interface. Ou et al carried out MD simulations of guanidinium and methylguanidinium chloride solutions using a polarizable CHARMM fluctuating charge force field, 28,29 and reported that both Gdm + and M-Gdm + ions deplete from air/water interface and lie parallel to the surface.…”
Section: Introductionmentioning
confidence: 63%
“…The key result from HD-VSFG measurements is an ensemble averaged D value determined by the orientation of the M-Gdm + methyl group at the air/water interface 24 D = cos 3 θ CH 3 cos θ CH 3 (1) , where θ CH 3 is the angle between the methyl C 3 axis and the surface normal. Another variable to describe the molecular orientation of M-Gdm + at the interface would be the angle θ MP between the molecular plane and the surface normal.…”
Section: Molecular Orientationmentioning
confidence: 99%